2021
DOI: 10.1002/bmc.5218
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for the quantification of anlotinib in human plasma using two‐dimensional liquid chromatography

Abstract: A simple, efficient, and stable detection method of two-dimensional liquid chromatography (2D-LC) was established and validated to determine anlotinib in the human plasma. The 2D-LC system comprises a first-dimensional column (LC1), an intermediate transfer column, and a second-dimensional column (LC2). With simple protein precipitation treatment, the samples were processed directly for detection. The analysis cycle time was completed within 9.50 min. For the anlotinib concentrations, the calibration curve was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 18 publications
2
4
1
Order By: Relevance
“…The clinical results showed that in the 10 mg dose of TC patients, the mean peak concentration of anlotinib in women was 109.5 ng·ml −1 , which was much higher than the value of 73.5 ng·ml −1 in men. This also confirms the conclusion of Li et al (2021) that under the same treatment conditions, the plasma concentration of female patients is higher than that of male patients. At the same time, we also found that at a dose of 12 mg in all female patients, the average blood concentration of TC patients was 118.8 ng·ml −1 , which was much higher than that of BC patients at 87.1 ng·ml −1 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The clinical results showed that in the 10 mg dose of TC patients, the mean peak concentration of anlotinib in women was 109.5 ng·ml −1 , which was much higher than the value of 73.5 ng·ml −1 in men. This also confirms the conclusion of Li et al (2021) that under the same treatment conditions, the plasma concentration of female patients is higher than that of male patients. At the same time, we also found that at a dose of 12 mg in all female patients, the average blood concentration of TC patients was 118.8 ng·ml −1 , which was much higher than that of BC patients at 87.1 ng·ml −1 .…”
Section: Discussionsupporting
confidence: 91%
“…The clinical results showed that in the 10 mg dose of TC patients, the mean peak concentration of anlotinib in women was 109.5 ngÁml À1 , which was much higher than the value of 73.5 ngÁml À1 in men. This also confirms the conclusion of Li et al (2021) that under the same treatment conditions, the plasma concentration of female patients is higher than that of male patients.…”
Section: Application Of the Methods For Monitoring Anlotinib Plasma C...supporting
confidence: 89%
See 1 more Smart Citation
“…ANL is mainly metabolized by CYP1A2 and CYP3A4/5 and secondary metabolic enzymes including CYP2C9, CYP2C19 and CYP2D6 (12, 13). Dexamethasone is a moderate inducer of CYP3A, which could accelerate the metabolism of ANL and reduce exposure (14). CYP2C19 rs3814637 and rs11568732 gene polymorphisms may also influence the ANL exposure (15).…”
Section: Introductionmentioning
confidence: 99%
“…CYP2C19 rs3814637 and rs11568732 gene polymorphisms may also influence the ANL exposure (15). In addition, Li et al and Yu et al has been reported that ANL plasma concentration is higher in female patients than male patients under the same dose (14,16). Beside these known contributions to variability in ANL exposure, patient characteristics such as age, body mass index, renal function and liver function may also contribute to variability in ANL exposure.…”
Section: Introductionmentioning
confidence: 99%